Role of Sex on the Clinical Outcomes of Coronary Artery Diseases Treated with Drug-Eluting Stents - Batth, Prabjot K; Alsabri, Mohammed (Cardiovascular Journal, 2022)
Background: With consideration of differing cardiac characteristics between women and men, such as coronary vessel sizes, this study was constructed to investigate if sex-based differences are present following drug-eluting stent implantation. Methods: Using PubMed and MeSH search tags, published data analyzing the potential sex differences in clinical outcomes following drug-eluting stent implantation was collected. Results: As compared to male patients, women had similar incidences of major adverse cardiac events and stent thrombosis at long-term follow-up despite being found to consistently have smaller vessels, higher incidences of advanced age, diabetes mellitus, and hypertension at hospital admission. At short-term follow-up, however, women had an increase of major adverse cardiac events as compared to men with complex lesions. Furthermore, height may play a role in clinical outcomes following treatment with a drug-eluting stent. Additionally, women may have superior healing responses with lower neointimal obstruction and lower maximum cross-sectional narrowing following drugeluting stent implantation. Conclusions: When differing baseline characteristics were corrected for with multivariate analysis, drug-eluting stents demonstrate similar clinical outcomes in women and men at long-term follow-up. Cardiovasc j 2022; 14(2): 157-167